Abstimmung in Bewegung: Intersubjektivität im Tango Argentino - Haller, Melanie (transcript, 2014)
In which ways can processes of coordination in tango be explained? Using a micro-analysis of Argentinian Tango dance practices, Melanie Haller works out these processes and presents them in relation to the discourses around tango. The trans-cultural dance culture of tango proves to be a practice of intersubjectivity processes: moments of coordination achieved by subjects dancing together that transcend their own – perceived as separate - subjectivity, bringing about the experience of intersubjectivity.